The Impact of Corporate Social Responsibility on Company Profitability And Environmental Sustainability - Safitrih, Nurul Amalia; Maulana, Moch Abid Athoillah; Hwihanus, Hwihanus (Business and Investment Review, 2024)
Companies use social and environmental issues in their commercial operations as part of the CSR management philosophy. CSR is regarded as both a means of achieving sustainable development and a gauge of a business's overall performance. This study aims to analyze the impact of Corporate Social Responsibility (CSR) on company profitability and environmental sustainability. This research was prepared using a meta-analysis approach, this method combines several studies or journals in a research chosen as the research object. Researchers systematically draw conclusions from journals obtained through international journals regarding "The Impact of Corporate Social Responsibility". Of the five journals that we analyzed, it shows that the impact of corporate social responsibility on company profitability and environmental sustainability has an influence, but there is a difference in that CSR has no effect on profitability. It is hoped that the results of this analysis will provide useful knowledge for policy makers, economic practitioners and other stakeholders in planning the CSR concept. This research paves the way for future researchers to examine more deeply the impact of CSR on company profitability and environmental sustainability.